Biodegradable composite material filled with straw powder and preparation method thereof

By using straw powder and other functional components, the shortcomings in the degradation rate and mechanical properties of existing materials are solved, and efficient utilization of agricultural waste is achieved, and the biodegradation rate and mechanical properties of the materials are significantly improved.

CN119570120APending Publication Date: 2025-03-07HANGSHI TECH DEV (HANGZHOU) CO LTD

Patent Information

Application Number
CN202411747402.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-01
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing biodegradable composites have shortcomings in degradation speed and mechanical properties, and it is difficult to effectively utilize agricultural waste, which increases the environmental burden.

Method used

Straw powder is used as the main filling material, combined with starch-based plastic, nanotitanium dioxide, nanomontmorillonite, biomass charcoal and other components, and the impurities are removed through high-pressure steam treatment and multi-step pretreatment to improve the purity and biodegradability of straw powder.

Benefits of technology

It significantly improves the mechanical properties and biodegradation rate of composite materials, reduces environmental pollution, reduces raw material costs, and conforms to environmental protection concepts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005164099400000091
    Figure BDA0005164099400000091
  • Figure BDA0005164099400000101
    Figure BDA0005164099400000101
  • Figure BDA0005164099400000121
    Figure BDA0005164099400000121
Patent Text Reader

Abstract

The invention discloses a straw powder filled biodegradable composite material and a preparation method thereof, and relates to the technical field of biodegradable composite materials, the preparation method of the biodegradable composite material comprises the following steps: S1, pretreating straw; s2, impurities are removed through winnowing; s3, removing magnetic impurities; s4, cleaning and drying; s5, performing high-pressure steam treatment; s6, drying in the oven and crushing again; s7, adding into a high-speed mixer and mixing; s8, extruding the biodegradable composite material, and cooling and shaping the biodegradable composite material; and S9, cutting and polishing are conducted, and performance testing is conducted. The biodegradable composite material is prepared from agricultural waste, waste accumulation is reduced, sustainable development is promoted, the straw powder filled biodegradable composite material has biodegradability, high strength and good processability, and the straw powder filled biodegradable composite material is suitable for large-scale production. The problems of reducing agricultural wastes, enhancing mechanical properties and environmental protection performance, improving processability and reducing raw material cost can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biodegradable composite materials, in particular to a biodegradable composite material filled with straw powder and a preparation method thereof. Background Art

[0002] Traditional biodegradable composite materials do not degrade fast enough in the natural environment, and the degradation conditions are relatively harsh, resulting in the inability to promptly and effectively convert waste into natural materials, thereby increasing the environmental burden. In addition, traditional biodegradable composite materials have poor mechanical properties. The biodegradable composite materials prepared in this application effectively utilize agricultural waste as raw materials, which not only reduces the difficulty of agricultural waste treatment, but also realizes the recycling of resources, improves the mechanical properties of composite materials, and improves the processing performance of composite materials. The composite materials do not produce harmful substances during the degradation process, and the degradation rate is fast and the degradation is thorough, thereby realizing green production and use.

[0003] The defects of existing biodegradable composite materials are:

[0004] 1. Patent document US8691893B2 discloses a method for preparing a biodegradable composite material. The document mainly considers how to improve the properties and cost of the composite material, but does not consider how to reduce agricultural waste, enhance mechanical properties, improve processing properties, improve the environmental performance of the composite material, and reduce the cost of raw materials;

[0005] 2. Patent document JP6944686B2 discloses a biodegradable composite material and a preparation method thereof. The document mainly considers how to solve the problem of lack of mechanical properties due to multiphase interface compatibility and high cost, but does not consider how to improve the antibacterial and antifouling properties of the composite material, enhance the mechanical properties and stability of the composite material, promote the biodegradability of the composite material, and improve the antioxidant and light aging resistance of the composite material;

[0006] 3. Patent document US8859690B2 discloses a biodegradable composite material, a preparation method thereof and a disposable product made thereof. The document mainly considers how to improve the toughness and heat resistance of polylactic acid, but does not consider how to improve the purity and consistency of the composite material, improve processing efficiency and molding quality, and reduce safety hazards;

[0007] 4. Patent document CN114634691B discloses a fully biodegradable composite material and a preparation method thereof. The document mainly considers how to simultaneously take into account the flexibility, weather resistance and halogen-free flame retardant properties of the composite material, but does not consider how to improve the biodegradability of straw, improve the crushing effect and uniformity of straw, remove some harmful substances and residues, optimize the processing performance of the composite material, and improve the physical and mechanical properties of the composite material. Summary of the invention

[0008] The object of the present invention is to provide a biodegradable composite material filled with straw powder and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0009] To achieve the above object, the present invention provides the following technical scheme: a biodegradable composite material filled with straw powder, wherein the raw materials include the following components: 30-50 parts of reed straw, 20-30 parts of wheat straw, 20-30 parts of corn straw, 10-20 parts of rice straw, 60-70 parts of starch-based plastic, 1-2 parts of zinc stearate, 8-10 parts of tributyl citrate, 3-5 parts of silane coupling agent, 10-20 parts of hemp fiber, 10-20 parts of bamboo fiber, 1-3 parts of nano titanium dioxide, 3-5 parts of nano montmorillonite, 6-8 parts of biochar, 1-2 parts of vitamin E, 1-2 parts of ultraviolet absorber, and 1-2 parts of hindered amine light stabilizer;

[0010] The preparation method of the biodegradable composite material is as follows:

[0011] S1, pre-treating the straw;

[0012] S2, removing impurities from reed straw, wheat straw, corn straw and rice straw by air separation;

[0013] S3, sending the straw segments after winnowing to a permanent magnetic drum magnetic separator to remove magnetic impurities;

[0014] S4, putting the magnetically separated straw segments into a cleaning container, stirring and soaking them for several times until there are no obvious impurities in the water, draining the water and sending them into an oven for drying;

[0015] S5, setting pressure, temperature and time to perform high-pressure steam treatment on reed straw, wheat straw, corn straw and rice straw respectively, and cooling, washing and drying to a moisture content of less than 8% after treatment;

[0016] S6, after the straw segments are crushed and screened, they are oven-dried and crushed again;

[0017] S7, adding straw powder and other raw materials into a high-speed mixer for mixing;

[0018] S8, adding the mixed materials into a twin-screw extruder to extrude the biodegradable composite material and cooling it to shape;

[0019] S9: Cut and grind the finalized biodegradable composite material and conduct performance test.

[0020] Preferably, S1 further includes the following:

[0021] S11: Straw includes reed straw, wheat straw, corn straw and rice straw;

[0022] S12: Use a sieve with an aperture of 10 cm to remove larger impurities in the straw, and then use a sieve with an aperture of 5 cm to further remove impurities, and then use a cutter to cut the straw into 15-20 cm straw segments.

[0023] Preferably, S3 further includes the following:

[0024] S31: feeding the wind-selected straw segments into the feed port of a permanent magnetic drum magnetic separator. The permanent magnetic drum magnetic separator generates a magnetic field through a rotating drum, and adsorbs magnetic impurities on the surface of the drum. As the drum rotates, the magnetic impurities are brought to a magnetic field-free area and automatically fall off.

[0025] S32: The straw segments with magnetic impurities removed are discharged from the discharge port, and a magnet is used to detect whether there are any residual magnetic impurities. If magnetic impurities are still found, magnetic separation is performed again.

[0026] Preferably, S4 further includes the following:

[0027] S41: Put the magnetically separated straw segments into a cleaning container, immerse the straw segments completely in water, stir the straw segments with a stirrer for 10 minutes, and then continue to soak for 20 minutes. Pour out the soaking water, add clean water again, stir and soak again, and repeat three times until there is no obvious impurities in the cleaned water.

[0028] S42: taking the cleaned straw segments out of the water, placing them on a sieve and waiting for the straw segments to drain naturally, and when no obvious liquid drips, sending the straw segments into an oven for drying to a moisture content of 10%-12%, and the oven drying temperature is 55°C.

[0029] Preferably, S5 further includes the following:

[0030] S51: Put the straw segments into a steam explosion tank, pass high-temperature and high-pressure steam, and perform high-pressure steam treatment. After the treatment is completed, quickly release the steam pressure, then take out the straw, cool it naturally to room temperature, wash it with clean water, and put it into a drying oven for drying treatment, so that the moisture content of the straw is reduced to less than 8%.

[0031] Preferably, S5 further includes the following:

[0032] S52: The pressure of high-pressure steam treatment of reed straw and corn straw is 2.2-2.5MPa, the temperature is 240-250℃, the high-pressure steam treatment time is 3-5min, and the temperature of drying treatment of cleaned reed straw in a drying oven is 65-70℃;

[0033] S53: The pressure of high-pressure steam treatment for wheat straw is 1.7-2.0 MPa, the temperature is 180-190°C, the high-pressure steam treatment time is 4-6 min, and the temperature of drying treatment for washed reed straw in a drying oven is 64-67°C;

[0034] S54: The pressure of the high-pressure steam treatment of the rice straw is 1.3-1.6 MPa, the temperature is 190-200° C., the high-pressure steam treatment time is 5-7 min, and the temperature of the drying treatment of the cleaned reed straw in the drying oven is 60-63° C.

[0035] Preferably, S6 further includes the following:

[0036] S61: feeding the dried straw segments into the feed port of a blade crusher, where the straw is cut and impacted by high-speed rotating blades and crushed into straw particles, which are then separated by screening through a 4 mm pore size screen. Straw particles that meet the requirements fall into a collecting device through the screen, while larger straw particles remain above the screen and are crushed again;

[0037] S62: The crushed straw particles are sent to an oven at a drying temperature of 55°C. After drying to a moisture content of 4%-6%, the straw particles are taken out and sent to a feed port of a hammer mill to be crushed into straw powder. The powder is sieved and separated through a sieve with an aperture of 0.3 mm. The straw powder that meets the requirements falls into a collecting device through the sieve, while the larger straw particles remain above the sieve for further crushing.

[0038] Preferably, S7 further includes the following:

[0039] S71: adding straw powder, starch-based plastic, zinc stearate, tributyl citrate, silane coupling agent, hemp fiber, bamboo fiber, nano titanium dioxide, nano montmorillonite, biochar, vitamin E, ultraviolet absorber and hindered amine light stabilizer into a high-speed mixer, starting the mixer, running it at 1000-1400 rpm for 2-3 minutes for preliminary mixing, then increasing the speed to 2500-2800 rpm, and continuing mixing for 15-20 minutes;

[0040] S72: The length of hemp fiber and bamboo fiber is 3-5 mm, the particle size of nano titanium dioxide is 60-80 nm, the particle size of nano montmorillonite is 40-50 nm, and the particle size of biochar is 150-160 mesh.

[0041] Preferably, S8 further includes the following:

[0042] S81: Set the temperature of the twin-screw extruder to between 150-160°C and the screw speed to 300-400 rpm.

[0043] Preferably, S9 further includes the following:

[0044] S91: Mechanical properties tests include tensile strength test, bending strength test and impact strength test;

[0045] S92: Degradability test using soil landfill method and composting method

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] 1. In the preparation of the biodegradable composite material, 30-50 parts of reed straw, 20-30 parts of wheat straw, 20-30 parts of corn straw, 10-20 parts of rice straw, 10-20 parts of hemp fiber and 10-20 parts of bamboo fiber are added. These straws and fibers are derived from agricultural waste. By converting them into valuable composite materials, the accumulation and burning of agricultural waste can be reduced, thereby reducing environmental pollution. Moreover, these plant fibers are renewable, so using them as raw materials for composite materials is helpful to promote sustainable development and reduce dependence on non-renewable resources. At the same time, the addition of reed straw, wheat straw, corn straw, rice straw, hemp fiber and bamboo fiber can enhance the tensile strength, flexural strength and impact strength of the composite material. In particular, the long fiber form of the reed straw, which has a relatively high strength, can effectively enhance the overall mechanical properties of the composite material. Biodegradable composite materials made of reed straw, wheat straw, corn straw, rice straw, hemp fiber and bamboo fiber are not only biodegradable, but also have excellent mechanical properties and processing properties due to their diverse fiber components. Therefore, they can be widely used in packaging, tableware, building materials, automotive interior and exterior decoration and other fields. Moreover, with the increasing global requirements for environmental protection, biodegradable composite materials are favored due to their environmental protection characteristics. Adding a variety of plant fibers not only conforms to the concept of environmental protection, but also can meet the requirements of material performance in different application scenarios. Compared with traditional composite materials, using agricultural waste and plant fibers as raw materials can significantly reduce production costs. The collection, pretreatment and processing of straw and fiber will also create more employment opportunities and promote local economic development. Therefore, it can solve the problems of reducing agricultural waste, enhancing mechanical properties, improving processing performance, improving the environmental performance of composite materials and reducing raw material costs.

[0048] 2. When preparing the biodegradable composite material, the present invention adds 1-3 parts of nano titanium dioxide, 3-5 parts of nano montmorillonite, 6-8 parts of biochar, 1-2 parts of vitamin E, 1-2 parts of ultraviolet absorber, and 1-2 parts of hindered amine light stabilizer. Nano titanium dioxide has a broad-spectrum antibacterial property, can inhibit bacterial growth and reproduction, and even decompose endotoxins produced after bacterial death. Adding it to the composite material can significantly improve the antibacterial ability of the material, reduce the survival rate of bacteria on the surface of the material, and reduce the risk of cross infection. Nano montmorillonite, as an inorganic nano material, can significantly enhance the mechanical properties of the material after being composited with the biodegradable matrix, including tensile strength, flexural strength and impact strength. At the same time, nano montmorillonite can also improve the thermal stability and barrier properties of the material and extend the service life of the material. Biochar has a large specific surface area and adsorption capacity, can be used as a carrier of microorganisms, promote the attachment and growth of microorganisms on the surface of the material, thereby accelerating the biodegradation process of the material. The addition of biochar helps the material to be decomposed by microorganisms faster in the natural environment, reducing environmental pollution. Vitamin E, as a powerful antioxidant, can inhibit free The generation and chain reaction of radicals can protect the material from oxidative damage. Adding vitamin E to the composite material can significantly improve the antioxidant performance of the material and extend the service life of the material. The ultraviolet absorber can absorb the ultraviolet part in the sunlight and fluorescent light source to prevent ultraviolet rays from damaging the material. The addition of ultraviolet absorbers can significantly improve the light aging resistance of the material and maintain the appearance and mechanical properties of the material. The hindered amine light stabilizer inhibits the photooxidation and light aging process by capturing free radicals, quenching singlet oxygen chromophores and decomposing peroxides. When used in conjunction with ultraviolet absorbers, it can more effectively improve the light aging resistance of the material. The addition of these additives not only improves the various properties of the composite material, but also makes the material more stable during the processing process, easy to shape and process. At the same time, due to the improvement of performance, the application scope of the composite material has also been broadened, and it can be applied to more fields with high requirements for material performance. Therefore, it can solve the problems of improving the antibacterial and antifouling properties of the composite material, enhancing the mechanical properties and stability of the composite material, promoting the biodegradability of the composite material, and improving the antioxidant and light aging resistance of the composite material.

[0049] 3. The present invention pre-treats the straw and removes impurities by air separation and magnetic separation. The large impurities in the straw, including soil and stones, etc., can be effectively removed by using screens with different apertures. If these impurities remain in the composite material, their performance will be reduced and the degradation rate will be affected. Further, light impurities and magnetic impurities in the straw can be removed by air separation and magnetic separation. Light impurities include dust and debris, etc., and magnetic impurities include iron nails and iron wires, etc., which also have an adverse effect on the performance of the composite material. Cutting the straw into 15-20 cm segments is beneficial to the subsequent crushing and mixing process, ensuring that the straw powder The uniform distribution of straw in the composite material improves the overall performance of the composite material. Through the steps of air separation and magnetic separation, the purity of the straw can be significantly improved, and the performance fluctuations and potential safety hazards of the composite material caused by the presence of impurities can be reduced, which is essential for the production of high-quality and high-stability biodegradable composite materials. The pretreated straw is more easily crushed into fine powder, which is convenient for uniform mixing with other components such as starch-based plastics, thereby improving the processing performance and molding quality of the composite material. Therefore, it can solve the problems of improving the purity and consistency of the composite material, improving the processing efficiency and molding quality, and reducing safety hazards.

[0050] 4. The present invention performs high-pressure steam treatment on reed straw, wheat straw, corn straw and rice straw respectively by setting pressure, temperature and time, and cools, washes and dries to a moisture content of less than 8% after treatment. The high-pressure steam treatment can destroy the lignin and hemicellulose structure in the cell wall of the straw, making the cellulose more easily exposed and decomposed, which helps microorganisms to more easily decompose the straw in the subsequent biodegradation process, thereby improving the biodegradation rate and efficiency of the composite material. At the same time, the high-pressure steam treatment can soften the straw, making it easier to crush it into fine powder, which not only improves the fineness of the straw powder, but also helps the uniform distribution of the straw powder in the composite material, thereby improving the overall performance of the composite material, and the high temperature environment of the high-pressure steam treatment can kill the straw. The cleaning step after high-pressure steam treatment can further remove impurities and residues on the surface of the straw to ensure the purity of the straw powder. The drying treatment reduces the moisture content of the straw to below 8%, which helps to reduce the evaporation and shrinkage of the composite material during processing and improve the stability and efficiency of the processing. The treated straw powder has enhanced adhesion with other components such as starch-based plastics, which is beneficial to the molding and curing of the composite material. Therefore, it can solve the problems of improving the biodegradability of the straw, improving the crushing effect and uniformity of the straw, removing some harmful substances and residues, optimizing the processing performance of the composite material, and improving the physical and mechanical properties of the composite material. DETAILED DESCRIPTION

[0051] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] Embodiment 1:

[0053] A straw powder filled biodegradable composite material, characterized in that the raw materials include the following components: 50 parts of reed straw, 30 parts of wheat straw, 30 parts of corn straw, 20 parts of rice straw, 70 parts of starch-based plastic, 2 parts of zinc stearate, 10 parts of tributyl citrate, 5 parts of silane coupling agent, 20 parts of hemp fiber, 20 parts of bamboo fiber, 3 parts of nano titanium dioxide, 3 parts of nano montmorillonite, 6 parts of biochar, 1 part of vitamin E, 1 part of ultraviolet absorber, and 2 parts of hindered amine light stabilizer.

[0054] Embodiment 2:

[0055] A straw powder filled biodegradable composite material, characterized in that the raw materials include the following components: 50 parts of reed straw, 30 parts of wheat straw, 20 parts of corn straw, 10 parts of rice straw, 70 parts of starch-based plastic, 2 parts of zinc stearate, 10 parts of tributyl citrate, 5 parts of silane coupling agent, 20 parts of hemp fiber, 20 parts of bamboo fiber, 3 parts of nano titanium dioxide, 3 parts of nano montmorillonite, 6 parts of biochar, 1 part of vitamin E, 1 part of ultraviolet absorber, and 2 parts of hindered amine light stabilizer.

[0056] Embodiment three:

[0057] A straw powder filled biodegradable composite material, characterized in that the raw materials include the following components: 50 parts of reed straw, 30 parts of wheat straw, 30 parts of corn straw, 10 parts of rice straw, 70 parts of starch-based plastic, 2 parts of zinc stearate, 10 parts of tributyl citrate, 5 parts of silane coupling agent, 20 parts of hemp fiber, 10 parts of bamboo fiber, 3 parts of nano titanium dioxide, 3 parts of nano montmorillonite, 6 parts of biochar, 1 part of vitamin E, 1 part of ultraviolet absorber, and 2 parts of hindered amine light stabilizer.

[0058] Embodiment 4:

[0059] A straw powder filled biodegradable composite material, characterized in that the raw materials include the following components: 50 parts of reed straw, 30 parts of wheat straw, 20 parts of corn straw, 20 parts of rice straw, 70 parts of starch-based plastic, 2 parts of zinc stearate, 10 parts of tributyl citrate, 5 parts of silane coupling agent, 20 parts of hemp fiber, 10 parts of bamboo fiber, 3 parts of nano titanium dioxide, 3 parts of nano montmorillonite, 6 parts of biochar, 1 part of vitamin E, 1 part of ultraviolet absorber, and 2 parts of hindered amine light stabilizer.

[0060] Embodiment five:

[0061] A straw powder filled biodegradable composite material, characterized in that the raw materials include the following components: 70 parts of starch-based plastic, 2 parts of zinc stearate, 10 parts of tributyl citrate, 5 parts of silane coupling agent, 20 parts of hemp fiber, 10 parts of bamboo fiber, 3 parts of nano titanium dioxide, 3 parts of nano montmorillonite, 6 parts of biochar, 1 part of vitamin E, 1 part of ultraviolet absorber, and 2 parts of hindered amine light stabilizer.

[0062] Furthermore, the biodegradable composite materials filled with straw powder prepared by the raw material components of Example 1, Example 2, Example 3 and Example 4 are material 1, material 2, material 3, material 4 and material 5, respectively. Material 5 is the control group. Performance tests are performed on material 1, material 2, material 3, material 4 and material 5. Each group of materials is tested 4 times and the average value is taken.

[0063] Further, the mechanical properties test includes tensile strength test, bending strength test and impact strength test;

[0064] The mechanical properties test results of Material 1 are as follows:

[0065]

[0066]

[0067] The mechanical properties test results of Material 2 are as follows:

[0068] Grouping Tensile strength(MPa) Bending strength(MPa) <![CDATA[Impact strength (kJ / m 2 )]]> 1 24.8 39.5 34.5 2 24.9 39.7 34.3 3 24.7 39.3 34.7 4 24.6 39.6 34.6 average value 24.75 39.53 34.53

[0069] The mechanical properties test results of Material 3 are as follows:

[0070] Grouping Tensile strength(MPa) Bending strength(MPa) <![CDATA[Impact strength (kJ / m 2 )]]> 1 26.0 41.0 36.0 2 26.2 41.2 35.8 3 25.9 40.8 36.2 4 26.1 41.1 35.9 average value 26.05 41.03 35.98

[0071] The mechanical properties test results of Material 4 are as follows:

[0072] Grouping Tensile strength(MPa) Bending strength(MPa) <![CDATA[Impact strength (kJ / m 2 )]]> 1 24.5 39.0 34.0 2 24.6 39.2 33.8 3 24.4 38.8 34.2 4 24.3 39.1 33.9 average value 24.45 39.03 33.98

[0073] The mechanical properties test results of Material 5 are as follows:

[0074] Grouping Tensile strength(MPa) Bending strength(MPa) <![CDATA[Impact strength (kJ / m 2 )]]> 1 18.0 30.0 25.0 2 18.2 30.2 24.8 3 17.9 29.8 25.2 4 18.1 30.1 24.9 average value 18.05 30.03 25.00

[0075] The results of mechanical properties test show that in terms of tensile strength, the average tensile strengths of materials 1 to 4 were 25.15 MPa, 24.75 MPa, 26.05 MPa and 24.45 MPa, respectively, which were significantly higher than 18.05 MPa of material 5, indicating that the addition of straw powder effectively improved the tensile properties of the composite material, enabling it to withstand greater tensile force without breaking easily.

[0076] In terms of bending strength, the average bending strengths of materials 1 to 4 were 40.53 MPa, 39.53 MPa, 41.03 MPa and 39.03 MPa respectively, while the average bending strength of material 5 was only 30.03 MPa. The average bending strength of materials 1 to 4 was also significantly higher than that of material 5, indicating that straw powder enhanced the bending resistance of the composite material, making it more durable.

[0077] In terms of impact strength, materials 1 to 4 also show obvious advantages, and their average impact strengths are 35.00 kJ / m 2 、34.53kJ / m 2 、35.98kJ / m 2 and 33.98 kJ / m 2 , much higher than 25.00 kJ / m of material 5 2 , indicating that the composite material filled with straw powder can better absorb energy, reduce damage and improve the impact resistance of the material when it is impacted.

[0078] In summary, the mechanical properties test results fully demonstrate the superiority of biodegradable composite materials filled with straw powder in mechanical properties, providing strong support for the wide application of these materials in agriculture, packaging, construction and other fields. At the same time, composite materials with different straw powder ratios show certain differences in mechanical properties, which provides a reference for further optimizing material formulations and improving material performance.

[0079] Furthermore, the degradation performance was tested using soil burial and composting methods;

[0080] The soil burial method test results are as follows:

[0081]

[0082] The composting test results are as follows:

[0083]

[0084] The results of soil burial test and composting test showed that the biodegradable composite materials 1-4 containing straw powder were significantly better than the control material 5 without straw powder in degradation performance;

[0085] In the soil burial test, the average degradation rates of materials 1, 2, 3 and 4 reached 30.15%, 29.43%, 30.85% and 29.70% respectively, which were much higher than the 14.53% of the control group material 5. This shows that the addition of straw powder significantly improves the biodegradability of the composite material.

[0086] In the composting test, the average degradation rates of materials 1, 2, 3 and 4 were also much higher than those of the control group, reaching 46.55%, 45.05%, 47.25% and 44.78% respectively, while the degradation rate of material 5 in the control group was only 24.55%, further confirming the effect of straw powder on improving the biodegradability of composite materials.

[0087] Judging from the results of four repeated tests of each material, the fluctuation range of the degradation rate is small, indicating that the degradation performance of these composite materials is relatively stable, repeatable and reliable.

[0088] Materials 1, 2, 3 and 4 differ in the type and ratio of straw powder, but all show good degradation performance, which indicates that adjusting the type and ratio of straw powder within a certain range can adjust the degradation rate of the composite material to a certain extent, but the overall degradation performance is better than that of materials without straw powder. Whether it is soil burial or composting, the composite materials containing straw powder show a high degradation rate, indicating that these materials have good biodegradability under different environmental conditions and have wide application potential.

[0089] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A biodegradable composite material filled with straw powder, characterized in that: The raw materials include the following components: 30-50 parts of reed straw, 20-30 parts of wheat straw, 20-30 parts of corn straw, 10-20 parts of rice straw, 60-70 parts of starch-based plastic, 1-2 parts of zinc stearate, 8-10 parts of tributyl citrate, 3-5 parts of silane coupling agent, 10-20 parts of hemp fiber, 10-20 parts of bamboo fiber, 1-3 parts of nano titanium dioxide, 3-5 parts of nano montmorillonite, 6-8 parts of biochar, 1-2 parts of vitamin E, 1-2 parts of ultraviolet absorber, and 1-2 parts of hindered amine light stabilizer; The preparation method of the biodegradable composite material is as follows: S1, pre-treating the straw; S2, removing impurities from reed straw, wheat straw, corn straw and rice straw by air separation; S3, sending the straw segments after winnowing to a permanent magnetic drum magnetic separator to remove magnetic impurities; S4, putting the magnetically separated straw segments into a cleaning container, stirring and soaking them for several times until there are no obvious impurities in the water, draining the water and sending them into an oven for drying; S5, setting pressure, temperature and time to perform high-pressure steam treatment on reed straw, wheat straw, corn straw and rice straw respectively, and cooling, washing and drying to a moisture content of less than 8% after treatment; S6, after the straw segments are crushed and screened, they are oven-dried and crushed again; S7, adding straw powder and other raw materials into a high-speed mixer for mixing; S8, adding the mixed materials into a twin-screw extruder to extrude the biodegradable composite material and cooling it to shape; S9: Cut and grind the finalized biodegradable composite material and conduct performance test.

2. The biodegradable composite material filled with straw powder and the preparation method thereof according to claim 1, characterized in that: S1 also includes the following: S11: Straw includes reed straw, wheat straw, corn straw and rice straw; S12: Use a sieve with an aperture of 10 cm to remove larger impurities in the straw, and then use a sieve with an aperture of 5 cm to further remove impurities, and then use a cutter to cut the straw into 15-20 cm straw segments.

3. The straw powder-filled biodegradable composite material and the preparation method thereof according to claim 1, characterized in that: S3 also includes the following: S31: feeding the wind-selected straw segments into the feed port of a permanent magnetic drum magnetic separator. The permanent magnetic drum magnetic separator generates a magnetic field through a rotating drum, and adsorbs magnetic impurities on the surface of the drum. As the drum rotates, the magnetic impurities are brought to a magnetic field-free area and automatically fall off. S32: The straw segments with magnetic impurities removed are discharged from the discharge port, and a magnet is used to detect whether there are any residual magnetic impurities. If magnetic impurities are still found, magnetic separation is performed again.

4. The straw powder-filled biodegradable composite material and the preparation method thereof according to claim 1, characterized in that: S4 also includes the following: S41: Put the magnetically separated straw segments into a cleaning container, immerse the straw segments completely in water, stir the straw segments with a stirrer for 10 minutes, and then continue to soak for 20 minutes. Pour out the soaking water, add clean water again, stir and soak again, and repeat three times until there is no obvious impurities in the cleaned water. S42: taking the cleaned straw segments out of the water, placing them on a sieve and waiting for the straw segments to drain naturally, and when no obvious liquid drips, sending the straw segments into an oven for drying to a moisture content of 10%-12%, and the oven drying temperature is 55°C.

5. The straw powder-filled biodegradable composite material and the preparation method thereof according to claim 1, characterized in that: S5 also includes the following: S51: Put the straw segments into a steam explosion tank, pass high-temperature and high-pressure steam, and perform high-pressure steam treatment. After the treatment is completed, quickly release the steam pressure, then take out the straw, cool it naturally to room temperature, wash it with clean water, and put it into a drying oven for drying treatment, so that the moisture content of the straw is reduced to less than 8%.

6. The straw powder-filled biodegradable composite material and the preparation method thereof according to claim 1, characterized in that: S5 also includes the following: S52: The pressure of high-pressure steam treatment of reed straw and corn straw is 2.2-2.5MPa, the temperature is 240-250℃, the high-pressure steam treatment time is 3-5min, and the temperature of drying treatment of cleaned reed straw in a drying oven is 65-70℃; S53: The pressure of high-pressure steam treatment for wheat straw is 1.7-2.0 MPa, the temperature is 180-190°C, the high-pressure steam treatment time is 4-6 min, and the temperature of drying treatment for washed reed straw in a drying oven is 64-67°C; S54: The pressure of the high-pressure steam treatment of the rice straw is 1.3-1.6 MPa, the temperature is 190-200° C., the high-pressure steam treatment time is 5-7 min, and the temperature of the drying treatment of the cleaned reed straw in the drying oven is 60-63° C.

7. The straw powder-filled biodegradable composite material and the preparation method thereof according to claim 1, characterized in that: S6 also includes the following: S61: feeding the dried straw segments into the feed port of a blade crusher, where the straw is cut and impacted by high-speed rotating blades and crushed into straw particles, which are then separated by screening through a 4 mm pore size screen. Straw particles that meet the requirements fall into a collecting device through the screen, while larger straw particles remain above the screen and are crushed again; S62: The crushed straw particles are sent to an oven at a drying temperature of 55°C. After drying to a moisture content of 4%-6%, the straw particles are taken out and sent to a feed port of a hammer mill to be crushed into straw powder. The powder is sieved and separated through a sieve with an aperture of 0.3 mm. The straw powder that meets the requirements falls into a collecting device through the sieve, while the larger straw particles remain above the sieve for further crushing.

8. The straw powder-filled biodegradable composite material and the preparation method thereof according to claim 1, characterized in that: S7 also includes the following: S71: adding straw powder, starch-based plastic, zinc stearate, tributyl citrate, silane coupling agent, hemp fiber, bamboo fiber, nano titanium dioxide, nano montmorillonite, biochar, vitamin E, ultraviolet absorber and hindered amine light stabilizer into a high-speed mixer, starting the mixer, running it at 1000-1400 rpm for 2-3 minutes for preliminary mixing, then increasing the speed to 2500-2800 rpm, and continuing mixing for 15-20 minutes; S72: The length of hemp fiber and bamboo fiber is 3-5 mm, the particle size of nano titanium dioxide is 60-80 nm, the particle size of nano montmorillonite is 40-50 nm, and the particle size of biochar is 150-160 mesh.

9. The straw powder-filled biodegradable composite material and the preparation method thereof according to claim 1, characterized in that: S8 also includes the following: S81: Set the temperature of the twin-screw extruder to between 150-160°C and the screw speed to 300-400 rpm.

10. The straw powder-filled biodegradable composite material and the preparation method thereof according to claim 1, characterized in that: S9 also includes the following: S91: Mechanical properties tests include tensile strength test, bending strength test and impact strength test; S92: The degradation performance test adopts soil landfill method and composting method.

Citation Information

Patent Citations

  • Fully biodegradable composite materials and their preparation methods

    CN114634691B

  • Packaging bag

    JP1988000063A

  • Biodegradable composite material and its manufacturing method

    JP6944686B2

  • Biodegradable composite materials

    US8691893B2

  • Biodegradable composite, the preparation process thereof, and a disposable article made therefrom

    US8859690B2

Cited By

  • Method for preparing high-strength flame-retardant environment-friendly composite material from silicon-rich biomass waste

    CN120248641A